Advancing Solid-State Batteries with Nanomaterials: Enhancing Safety, Performance, and Energy Efficiency - Lang Junbo (E3S Web of Conferences)
Solid-state batteries (SSBs) are a promising advancement in energy storage technology, offering higher energy density and improved safety compared to traditional lithium-ion batteries. The integration of nanomaterials into SSBs has the potential to overcome key technical challenges, including low ion conductivity, interface instability, and mechanical failures. This review explores the role of nanomaterials in enhancing the performance of SSBs by improving ion transport, stabilizing interfaces, and inhibiting dendritic crystal growth. Additionally, the application of nanoscale coatings on electrodes and solid electrolytes is discussed as a strategy to further optimize battery performance. While nanomaterials significantly improve the safety, efficiency, and longevity of SSBs, challenges such as large-scale production, cost control, and long-term stability remain. Continued research and innovation are essential to fully unlock the potential of nanomaterials in SSBs, which hold significant promise for sustainable energy storage solutions, particularly in electric vehicles and renewable energy systems.